Investigation of the influence of space weather on the occurrence of geoinduction currents in the middle latitudes - Nurgaliyeva, K. (Recent Contributions to Physics, 2023)
The study of physical processes based on geomagnetic induction currents among the geophysical problems of the last decade is one of the main problems of fundamental research. Consideration of geomagnetic-induced current as a threatening "shock" aspect originally took place in the NASA project "life with a star", and one of the main results of this working group was that the problems of geomagnetic-induced current must be solved in combination with science and methods. In the proposed work, calculations were carried out using a model of the same type, the model of which is based on the fundamental laws. The retrospective analysis of the geophysical situation for 2016-2021 was carried out on the basis of the data of the Alma-Ata geomagnetic observatory. For all the considered events, the GIC values were calculated and the peculiarities of the occurrence of GIC at middle latitudes were studied. Of all the events studied for 2016-2021, 25 events were identified. Among these events: 1 large geomatnetic storm, 1 medium geomagnetic storm, 5 substorms and 18 weak geomagnetic storms. For these events, the following was identified. During a large geomagnetic storm, the GIC amplitude value was I=0.4mA. During an average magnetic storm I=0.14mA. During a storm with a sudden onset induced current amplitude I=0.75mA. During weak magnetic storms, the amplitude values varied within (0.06 - 0.15)mA. In general, it can be seen, that the GIC amplitude values depend on the intensity of the geomagnetic storm. However, there are some exceptions. For example, a storm with a sudden onset according to the planetary index refers to weak geomagnetic storms, however, the GIC value turned out to be greater than the GIC induced during a large geomagnetic storm. At the same time, we also considered substorms. During substorms, currents of the order of 0.07-0.13mA were induced.